Learning Technology for Education in Cloud : 4th International Workshop, LTEC 2015, Maribor, Slovenia, August 24-28, 2015, Proceedings - Uden, Lorna; Liberona, Dario; Welzer, Tatjana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Fourth International Workshop on Learning Technology for Education in Cloud, LTEC 2015, held in Maribor, Slovenia, in August 2015. The 24 revised full papers presented were carefully reviewed and selected from 46 submissions. The papers cover various aspects of technologies for learning, such as MOOC challenges; cooperative learning; learning engineering; learning tools and environments; STEM.
Keywords: Education; Computer science; Computers and Education; Information Systems Applications (incl. Internet).; Computer Applications